Auriculotherapy as a means of managing nausea and vomiting in pregnancy: A double-blind randomized controlled clinical trial. (August 2020) - Negarandeh, Reza; Eghbali, Mohammad; Janani, Leila; Dastaran, Farzaneh; Saatchi, Kiarash
Abstract: Introduction: This study was aimed to assess the effectiveness of auriculotherapy on managing nausea and vomiting during pregnancy. Methods: In this randomized clinical trial, 128 pregnant women suffering from nausea and vomiting were selected and assigned to study groups. The data were collected using demographic information and Rhodes' questionnaires and analyzed in SPSS v.22. Results: After intervention, the average nausea score of the Rhodes index declined significantly in patients in the intervention group (p < 0.001).However, there was no significant (p = 0.305) difference between the two groups regarding vomiting. The results of the repeated measures showed that interventions had a significant effect on the total score of the questionnaire and also the scores regarding nausea (p < 0.04). Conclusion: The appropriate use of effective points on ears to control nausea and vomiting as a non-medicine and complementary treatment can alleviate nausea among pregnant women. Highlights: What is already known about the topic? Nausea and vomiting in pregnancy (NVP) is one of the most common complications of pregnancy. Ear acupressure using a magnet is a non-invasive, inexpensive, safe, and easy approach which is applicable by patients. Auriculotherapy is a treatment in traditional Chinese medicine that works by stimulating certain parts of the ear . What this paper adds Our results showed that ear acupressure can lead to a significant reduction in nausea in pregnant women. Based on the results of this study, it is suggested that health care providers recommend this method to pregnant mothers.